Burnt sugarcane harvesting work: effects on pulmonary and systemic inflammatory markers - Leite, Marceli Rocha; Trevisan Zanetta, Dirce Maria; Antonangelo, Leila; Marcal, Lia Junqueira; Ramos, Dionei [UNESP]; Burdmann, Emmanuel Almeida; Santos, Ubiratan Paula (Taylor & Francis Ltd, 2018)
Objective: To evaluate the effects of burnt sugarcane harvesting on the plasmatic and urinary concentrations of the club cell secretory protein (CC16) and inflammatory systemic biomarkers in a group of sugarcane cutters.Methods: Seventy-eight sugar cane workers were evaluated. The plasmatic and urinary concentrations of CC16, a pulmonary damage marker and inflammatory systemic biomarkers were collected at three time points: before, three months after and six months after the onset of the burnt sugarcane harvesting period. All evaluations were performed at approximate to 7 am, before the daily work shift. In the three-month evaluation, a post-work shift assessment (acute effect) was also performed.Results: The age of the workers was 37.911.0years. The PM2.5 concentrations were 27.0 (23.0-33.0) and 101.0 (31.0-139.5) mu g/m(3) in the pre harvest and harvest periods, respectively (p<.001). Burnt sugarcane harvesting was associated with a reduction, throughout the work during burnt sugarcane harvesting (subchronic effect), in plasmatic and urinary CC16 concentrations. Acutely, there was a decrease in plasmatic concentrations. There were acute and subchronic increases in inflammatory markers (neutrophils, monocytes) and muscle damage markers (CK and LDH) and a decrease in red blood cells.Conclusions: Harvesting of burnt sugarcane was associated with acute and subchronic reductions in the plasmatic and urinary concentrations of CC16 protein and changes in systemic inflammatory markers.
Keywords: Sugarcane harvest; sugarcane workers; CC16; inflammatory markers